2D VAN HOVE SUPERCONDUCTORS WITH WEAK AND STRONG-COUPLINGS - Parvin, F.; Islam, A.K. M.A.; Islam, F. N. (The Nucleus, 2020)
The critical temperature (Tc) and the isotope coefficient (Î±) of two-dimensional van Hove superconductors have been analyzed. The phonon induced superconductors with both weak and strong couplings are considered. For weak coupling, the variation of Tc and Î± as a function of average phonon frequency, Ï‰D, for three sets of pairing potential, V, shows that Î± decreases at nearly same rate with the increase of Ï‰D; but Tc increases with increasing Ï‰D but at different rates for different V. For strong coupling, the variation of Tc and Î± shows that smaller band width produces desirable results that are consistent with observation.